2011
DOI: 10.1074/jbc.m111.284844
|View full text |Cite
|
Sign up to set email alerts
|

Jumping Mode Atomic Force Microscopy on Grana Membranes from Spinach

Abstract: The thylakoid membrane system is a complex membrane system that organizes and reorganizes itself to provide plants optimal chemical energy from sunlight under different and varying environmental conditions. Grana membranes are part of this system and contain the light-driven water-splitting enzyme Photosystem II (PSII) and light-harvesting antenna complexes. Here, we present a direct visualization of PSII complexes within grana membranes from spinach. By means of jumping mode atomic force microscopy in liquid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 40 publications
8
40
0
Order By: Relevance
“…The distribution of PSII complexes in this membrane topograph mirrors the distribution of PSI in Figure 5; now the weak topographic features for the lumenal face of PSI are scarcely visible, but protruding water-oxidizing complexes make it possible to identify PSII. At the low resolution of the AFM topograph in Figure 6, the PSII dimer appears as a pair of 4.3 6 0.6 nm protrusions separated by 11.7 6 1.9 nm ( Figure 6D), consistent with previous AFM studies (Sznee et al, 2011;Johnson et al, 2014) and the structure of the water oxidizing component of the PSII core complex (Ferreira et al, 2004;Loll et al, 2005;Umena et al, 2011;Suga et al, 2015).…”
Section: T Elongatus Thylakoids With Psi Interspersed Among Other Cosupporting
confidence: 74%
See 1 more Smart Citation
“…The distribution of PSII complexes in this membrane topograph mirrors the distribution of PSI in Figure 5; now the weak topographic features for the lumenal face of PSI are scarcely visible, but protruding water-oxidizing complexes make it possible to identify PSII. At the low resolution of the AFM topograph in Figure 6, the PSII dimer appears as a pair of 4.3 6 0.6 nm protrusions separated by 11.7 6 1.9 nm ( Figure 6D), consistent with previous AFM studies (Sznee et al, 2011;Johnson et al, 2014) and the structure of the water oxidizing component of the PSII core complex (Ferreira et al, 2004;Loll et al, 2005;Umena et al, 2011;Suga et al, 2015).…”
Section: T Elongatus Thylakoids With Psi Interspersed Among Other Cosupporting
confidence: 74%
“…These analyses showed that the neighbors of PSI are likely to be PSII, as depicted in Figure 5D. The pronounced topology of the PSII water-oxidizing complex on the lumenal side of the membrane aids its identification in AFM topographs of plant thylakoids (Sznee et al, 2011;Johnson et al, 2014;Kirchhoff et al, 2008;Phuthong et al, 2015), but in our measurements, this side of the membrane adheres to the mica support and is not available for imaging. Figure 6 shows that, using a different method to immobilize membranes, PSII complexes can be imaged at low resolution, and they likely sit alongside PSI complexes.…”
Section: Discussionmentioning
confidence: 91%
“…The grana membranes are covered with topographic features protruding 3 to 5 nm from the surrounding membrane surface that are 16 to 20 nm in width, consistent with the structure of the lumenal protrusions of the PSII core complex (Zouni et al, 2001;Ferreira et al, 2004;Loll et al, 2005;Guskov et al, 2009;Umena et al, 2011;Sznee et al, 2011) (Figures 1A to 1C). The holes and frayed edges often evident in aG membranes ( Figure 1A) suggested a level of damage, as observed previously (van Roon et al, 2000;Sznee et al, 2011). Higher resolution images obtained on these membranes (Figures 1D to 1F) showed that the individual topographic features seen in Figures 1A to 1C are often resolved as two protrusions with maxima separated by ;8 nm.…”
Section: Resultsmentioning
confidence: 57%
“…Indeed, there is evidence that the distribution of cytb 6 f complexes is dynamically responsive to the PQ redox state, with an increase in the proportion found in the stromal lamellae under conditions where the PQ pool is reduced (Vallon et al, 1991). The absence of cytb 6 f complexes from Triton-and a-DM-derived grana membranes may be due to their selective solubilization by Triton and a-DM detergents, which could explain the holes frequently observed in these membranes and their generally ragged appearance (Dunahay et al, 1984;van Roon et al, 2000;Sznee et al, 2011). Indeed, cytb 6 f was solubilized from the membrane at lower concentrations of Triton than used for either PSI or PSII complexes (Morrissey et al, 1986).…”
Section: Cytb 6 F Complexes Are Distributed Throughout the Grana Membmentioning
confidence: 99%
See 1 more Smart Citation